Pengaruh Stres Kerja Terhadap Turnover Intention Dengan Kepuasan Kerja Sebagai Mediasi Pada Generasi Z Di DKI Jakarta - Ellisa Wahyuningrum; Ryan Basith Fasih Khan (Jurnal E-Bis, 2023)
This study aims to examine the effect of job stress on turnover intention through job satisfaction as mediation. The sample was selected using purposive sampling method, namely judgment sampling. The selected sample is Generation Z employees who work for both startup and non-startup companies in DKI Jakarta Province. The number of observations used was 115 employees. Sample data was tested using Structural Equation Modeling with the help of the SmartPLS 3.0 application. The test results show that there is a positive and significant influence between job stress on turnover intention, while job stress on job satisfaction has a significant negative effect. Then, there is a negative and insignificant influence between the relationship between job satisfaction and turnover intention. Then, there is no mediating effect of job satisfaction on the relationship between job stress and turnover intention.